2017
DOI: 10.1103/physrevb.95.214310
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between spatial coherence and temporal coherence of phonons

Abstract: Coherent phonon transport is regarded as a promising strategy for controlling thermal properties in solids using the wave nature of phonons. However, no clear distinction between the spatial and temporal phonon coherence has been accounted for and a formalism that quantifies these two effects is still to be found. In this work, we propose a statistical approach for calculating the spatial and temporal coherence spectra using molecular dynamics simulations. We provide a microscopic assessment of these propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Interestingly, wave packets follow a unimodal distribution as a function of coherence time, indicating the predominance and the limits in duration of a subpopulation centered at τ c ∼ 40 ps. The TAPND was not observed before, only its average on τ c obtained by other methods [8]. Previously, the founding work of Hardy [37] mentioned that the TAPND of a given mode k should be distributed along an ad hoc Gaussian function, i.e., D(k,…”
Section: B Coherence Time Distributionmentioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly, wave packets follow a unimodal distribution as a function of coherence time, indicating the predominance and the limits in duration of a subpopulation centered at τ c ∼ 40 ps. The TAPND was not observed before, only its average on τ c obtained by other methods [8]. Previously, the founding work of Hardy [37] mentioned that the TAPND of a given mode k should be distributed along an ad hoc Gaussian function, i.e., D(k,…”
Section: B Coherence Time Distributionmentioning
confidence: 90%
“…Previous studies also demonstrated that the particlelike and wavelike thermal phonons are coexisting at elevated temperature [4,4,[8][9][10]. In epitaxial oxide superlattices, Ravichandran et al [4] experimentally observed this mechanism and the predominant behavior depends on temperature and period.…”
Section: Introductionmentioning
confidence: 91%
“…is calculated to present the composition of the phonon energy of a frequency ω occupying the total energy. This definition of y is similar to that provided by Latour and Chalopin [44], where they proposed to use the cross-spectral density function, m |χ j,i (ω)| k b T , to represent the composition of phonons. When atoms i and j are the same atom, the ratio y becomes proportional to the phonon density of states.…”
Section: B Redistribution Effect Of Anharmonicity In Interfacial Sysmentioning
confidence: 91%
“…[200] More recently, Latour et al [201] proposed a microscopic theory of the phonon spatial coherence length based on correlation theory. In another work, Latour et al [221] used correlation theory to include spatial and temporal coherence, analyzing transport in a SL, defining coherent and incoherent transport regimes with relation to the phonon mean free path and the spatial coherence length.…”
Section: (19 Of 32)mentioning
confidence: 99%
“…[21,205,206,216] Although phonons can be generated from the heat source, [205] thermal phonons, as a result of the scattering processes required to reach equilibrium, are typically incoherent and controlling their phase relationship poses serious challenges. [221] In principle, non-equilibrium phonons can also be transferred across the interface between the heated and surrounding medium and this mechanism is still a subject of investigation. [180,222] These phonon excitation processes provide a potential ground to bridge plasmonics and phononics, as described in Section 4, where the focus will be on phonon generation in plasmonic (metallic) nanostructures.…”
Section: Summary Of Transport Regimesmentioning
confidence: 99%